EVALUATING THE LEGAL REGULATION OF PROPERTY EXPECTATIONS IN THE CONTEXT OF CONTRACTUAL OBLIGATIONS: A SYSTEMATIC LITERATURE REVIEW - Lutsenko , Dmytro; Sverdlichenko , Valentyna; Martyniuk , Oleksandr; Hura, Maksym; Meniv , Yaroslava (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
The protection of property expectations plays a crucial role in contemporary legal systems, particularly in the context of fulfilling contractual obligations. It promotes predictability and fairness in legal relations, establishing a framework for balancing private and public interests. In countries with transitional legal systems, such as Ukraine, property rights and contractual mechanisms face additional challenges as the global economy evolves. Given the difficulties outlined above, there is a pressing need for research into how legal systems adjust to the ever-changing political, social, and economic climates. Property expectations are essential for public policy, economic stability, and legal accountability. This study aims to conduct a systematic literature review (SLR) of existing studies on legally controlled expectations of property, with a particular focus on works published between 2019 and 2024. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework utilized in this study ensures openness and completeness of the process for selecting, excluding, and reviewing relevant material. Research was limited by the review scope, which included only peer-reviewed articles, reviews, and conference papers, ensuring the quality and credibility of the SLR. The findings of this study highlight research gaps, particularly in relation to socio-environmental factors and legislative changes in transition economies. In contrast, the current study emphasizes the need for an interdisciplinary approach to address existing gaps. By analyzing contemporary literature, it aims to enhance understanding among researchers and legislators regarding the interplay between property rights and legal obligations. JEL Classification Codes: K00, K11, K12, K33.